Community Vocational Training Center (BLKK) as a Model of Islamic Human Capital Development for Sustainable Development - Abdullah Kafabih; Hapsari Wiji Utami (Journal of Community Service and Rural Development, 2025)
This study explores the role of Community Vocational Training Centers (Balai Latihan Kerja Komunitas, BLKK) as a model of Islamic Human Capital Development in promoting sustainable development. Using a qualitative descriptive method with field observations and in-depth interviews at BLKK Mambaul Hikam (East Java), BLK Komunitas Bahrul Ulum (Southeast Sulawesi), and BLK Komunitas Al-Manaar (Central Java), the study examines how vocational training contributes not only to skill acquisition but also to community empowerment. The analysis employs the Islamic Human Development Index (IHDI), derived from the maqashid shariah dimensions: religion (dīn), life (nafs), intellect (‘aql), family (nasl), and wealth (māl). Findings reveal that BLKK plays a dual role: improving professional skills to meet market demands, and instilling ethical, spiritual, and social values aligned with sustainable development goals. The study concludes that integrating IHDI into vocational training provides a comprehensive framework for human capital development that is economically viable, socially inclusive, environmentally responsible, and spiritually grounded.